Anti-Bully Lesson di Pesantren Modern Al-Amanah Junwangi - Lutfi Arya; M. Husni Tamrin; Dimas Riztiardhana; Andi Maulida Rahmania (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Bullying has occurred in various types of schools, including Islamic boarding schools. The Al-Amanah Junwangi Modern Islamic Boarding School is no exception. Partners experience two problems: (1) teachers lack knowledge about bullying and its handling; and (2) students engage in bullying. Partners are aware of the dangers of bullying, so there is a need for an anti-bullying program. One solution is to provide knowledge and insight about bullying or anti-bullying lessons. To address the second problem, the solution is to implement anti-bullying lessons directly with students. We implemented the method by using lectures interspersed with questions and answers, discussions, viewing videos, games, case studies, and simulations. There were 46 anti-bullying lesson participants, with details of 16 teachers, 15 Santri, and 15 female students. The results of the implementation showed an increase in understanding about bullying and its impacts by 16% and an increase in practical sessions by 38% among teachers. Meanwhile, students showed an increase in understanding about bullying and its impacts by 19%, and female students by 10%. Other results show that female students are able to demonstrate behavior against bullying completely, while 58% of students are able to demonstrate stay-calm behavior, 33% feel good about you, and 75% don't be quite.